UJI EFIKASI EKSTRAK GULMA SIAM TERHADAP MORTALITAS HAMA PENCUCUK BUAH KAKAO (HELOPELTIS SPP.) DI LABORATORIUM - Yuyun Fitriana; . Purnomo; Agus M. Hariri (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
This research was aimed to investigate the effect of siam weeds (C. odorata) extract on the mortality of Helopeltis spp., the effect of the addition of emulsifier on the toxicity of siam weed extract, and to find out a potential concentration of the siam weeds extract that can be used as bioinsecticide for Helopeltis spp. Six concentration levels of C. odorata were used as treatments: 0% (control), 20%, 30%, 40%, 50% and 60% by adding 0.3% or no emulsifier. Data collected were mortality of nymphs and adults of Helopeltis spp. The results showed that the application of the siam weeds (C. odorata) extract was able to kill of nymph and adult of Helopeltis spp. The mortality of nymph ranged from 26.6% to 50.0% without emulsifier and 78.8% to 85.0% with emulsifier, and for adult range 15.00% - 46.67% without emulsifier and 31.67% - 71.67% with emulsifier for adult. The results confirm by adding emulsifier can enhance toxicity of siam weed extract to Helopeltis spp.. There was no significant effect of concentration level of siam weed on cocoa mirid mortality, therefore concentration level of 20% seems to be the potential concentration of siam weed extract that can be used as bioinsecticide of Helopeltis spp..